Diaryl alkene hydrogen bond organic framework single crystal as well as synthesis method and application thereof
By using diarene hydrogen bonded organic frame single crystal material, the excellent photochromic performance and efficient separation performance are used to solve the shortcomings of existing hydrogen bonded organic frame materials in photochromic and separation performance, and the separation effect is achieved with low energy consumption, efficient and environmentally friendly.
Patent Information
- Application Number
- CN202510101842.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-01-22
AI Technical Summary
The existing hydrogen bond organic frame materials have shortcomings in photochromic properties and separation properties, especially in the separation of pyridine and toluene, and traditional methods have problems such as high energy consumption and complex operation.
Using diarene hydrogen bonded organic frame single crystal, it is formed from 1,2-bis[2-methyl-3-thienyl-5-pyridine]perfluorocyclopentane and tetrafluoroterephthalic acid, and materials with excellent photochromic properties and efficient separation properties are prepared by reasonable synthesis methods.
It achieves rapid response and good reversible photochromic properties of the material, and shows efficient and environmentally friendly properties in the separation of pyridine and toluene, overcoming the problems of high energy consumption and complex operation of traditional methods.
Smart Images

Figure CN119775587A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrogen-bonded organic framework materials, and in particular relates to a diarylolefin hydrogen-bonded organic framework single crystal, a synthesis method thereof and applications thereof. Background Art
[0002] As an important functional material, organic solid-state photochromic materials are widely used in sensors, display technology, invisible materials and other fields. Diarylethenes have become a hot topic of research due to their excellent photochromic properties. Especially in the design and regulation of molecular structure, there is still a lot of room for improvement in the photochromic performance of diarylethenes. Therefore, how to improve the performance of materials through reasonable molecular engineering design, especially to regulate their photochromic behavior, is still a major challenge in the research of organic photochromic materials.
[0003] As an emerging class of functional materials, hydrogen-bonded organic frameworks (HOFs) have shown broad application prospects in many fields due to their tunable molecular structure and high stability. The interaction of hydrogen bonds provides them with excellent self-assembly ability and structural regulation potential. However, the application of existing hydrogen-bonded organic frameworks in photochromic materials is still immature. Although some studies have explored the photochromic properties of hydrogen-bonded organic frameworks, the instability of intermolecular hydrogen bonds and their sensitivity to the external environment have led to insufficient stability and controllability of these materials in practical applications.
[0004] In the field of separation science, separation of pyridine and toluene mixture is an important technology in chemical processes, and is widely used in the fields of fine chemicals and environmental protection. Traditional separation methods, such as solvent extraction, distillation and membrane separation, often have problems such as high energy consumption, complex operation and high cost, and are difficult to meet the growing demand for efficient separation. Summary of the invention
[0005] In view of the above-mentioned technical problems existing in the separation of a mixture of pyridine and toluene, the present invention proposes a diarylethene hydrogen-bonded organic framework single crystal, a synthesis method and an application thereof, which can prepare a material having both excellent photochromic properties and potential separation applications, and has good separation performance, high efficiency and environmental protection performance in the separation of mixtures.
[0006] In order to achieve the above-mentioned purpose, the technical scheme adopted by the present invention is: a diarylethene hydrogen bonded organic framework single crystal, a synthesis method thereof and an application thereof are provided by the present invention; wherein the diarylethene hydrogen bonded organic framework single crystal is assembled from 1,2-di[2-methyl-3-thienyl-5-pyridyl]perfluorocyclopentane (PDTE) and tetrafluoroterephthalic acid (TA); the diarylethene hydrogen bonded organic framework single crystal belongs to the monoclinic system, the space group is C2 / c, and the unit cell parameters are a=21.437(8)b=8.418(3)c=19.277(7); α=90°, β=114.343(6)°, γ=90°;
[0007] The structural formula of the 1,2-bis[2-methyl-3-thienyl-5-pyridyl]perfluorocyclopentane is:
[0008]
[0009] The structural formula of the tetrafluoroterephthalic acid is:
[0010]
[0011] The present invention provides a method for synthesizing a diarylethene hydrogen-bonded organic framework single crystal, comprising the following steps:
[0012] S1. Add a certain molar ratio of 1,2-di[2-methyl-3-thienyl-5-pyridine]perfluorocyclopentane (PDTE) and tetrafluoroterephthalic acid (TA) into a 100 mL single-necked flask, add a certain volume of an organic solvent into the flask, and heat for a certain period of time until the raw materials are completely dissolved to obtain a reaction solution;
[0013] S2. The reaction solution was cooled at room temperature and then filtered, and transferred into a 10 mL glass vial, which was sealed with plastic wrap. Appropriate small holes were pierced in the plastic wrap with a needle, and the solution was allowed to stand at room temperature for a period of time to evaporate, thereby obtaining a diarylethene hydrogen-bonded organic framework single crystal PDTE-TA.
[0014] Preferably, in step S1, the molar ratio of 1,2-di[2-methyl-3-thienyl-5-pyridyl]perfluorocyclopentane to tetrafluoroterephthalic acid is 1:1.
[0015] Preferably, the organic solvent is anhydrous ethanol, and the volume of the organic solvent is 3-5 mL.
[0016] Preferably, in step S1, the heating temperature is 70°C and the heating time is 9 hours.
[0017] Preferably, the number of small holes in the cling film is 1-8, and the hole diameter is less than 3 mm.
[0018] Preferably, the reaction solution is left to volatilize at room temperature for 9-14 days.
[0019] The invention provides an application of a diarylethene hydrogen-bonded organic framework single crystal. The diarylethene hydrogen-bonded organic framework single crystal is activated at 100° C. for 8 hours to obtain an activated crystal, and the activated crystal is used to separate polar and non-polar substances in a mixture liquid of polar and non-polar substances; the activated crystal is placed in the mixture liquid of polar and non-polar substances, and volatile gases are adsorbed and separated at room temperature, and the adsorption time is 0-44 hours.
[0020] Preferably, the polar and non-polar substance mixture liquid is a pyridine and toluene mixture liquid.
[0021] Compared with the prior art, the advantages and positive effects of the present invention are:
[0022] 1. The present invention provides a diarylethene hydrogen-bonded organic framework single crystal. When the diarylethene hydrogen-bonded organic framework single crystal is synthesized, it contains a diarylethene structure with photoswitchable characteristics. The diarylethene photochromic structural unit is not affected in the hydrogen-bonded organic framework and can still show photochromic characteristics. It has rapid response and good reversibility, thus overcoming the shortcomings of existing materials in terms of photochromic performance.
[0023] 2. The method for synthesizing a diarylethene hydrogen-bonded organic framework single crystal provided by the present invention has a reasonable design and a simple method, and is suitable for industrial-scale production.
[0024] 3. The application of a diarylethene hydrogen-bonded organic framework single crystal provided by the present invention can efficiently separate a liquid mixture of pyridine and toluene, overcoming the problems of high energy consumption and complex operation in traditional separation methods, and providing a low-energy, high-efficiency and environmentally friendly separation solution, and is also suitable for environmental protection, fine chemicals and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0026] Figure 1 The synthetic route of PDTE-TA prepared in Example 1 is shown in FIG.
[0027] Figure 2 is the crystal structure diagram of PDTE-TA prepared in Example 1;
[0028] Figure 3 This is the thermogravimetric diagram of PDTE-TA prepared in Example 1;
[0029] Figure 4is the infrared spectrum of PDTE-TA prepared in Example 1;
[0030] Figure 5 is the X-ray diffraction pattern of PDTE-TA prepared in Example 1;
[0031] Figure 7 is the ultraviolet absorption spectrum of PDTE-TA prepared in Example 1;
[0032] Figure 6 This is the nitrogen gas adsorption diagram of PDTE-TA prepared in Example 1;
[0033] Figure 8 The PDTE-TA prepared in Example 1 adsorbs pyridine and toluene vapor respectively. 1 H NMR;
[0034] Fig. 9 The time-dependent solid-gas adsorption isotherm of the mixed vapor of pyridine and toluene adsorbed by PDTE-TA prepared in Example 1;
[0035] Fig.10 is a gas chromatogram of the adsorption of pyridine and toluene mixed vapor by PDTE-TA prepared in Example 1;
[0036] Fig.11 This is the cyclic adsorption-regeneration diagram of the PDTE-TA prepared in Example 1 adsorbing the mixed vapor of pyridine and toluene. DETAILED DESCRIPTION
[0037] In order to more clearly understand the above-mentioned objects, features and advantages of the present invention, the present invention is further described below in conjunction with the accompanying drawings and embodiments. It should be noted that the embodiments of the present application and the features in the embodiments can be combined with each other without conflict. For the convenience of description, if the words "upper", "lower", "left" and "right" appear below, they only indicate that the upper, lower, left and right directions are consistent with the accompanying drawings themselves, and do not limit the structure.
[0038] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways than those described herein. Therefore, the present invention is not limited to the specific embodiments of the following disclosure.
[0039] Embodiment 1, as Figure 1As shown, the present invention provides a method for synthesizing a diarylethene hydrogen-bonded organic framework single crystal: S1, taking [1,2-di[2-methyl-3-thienyl-5-pyridine]perfluorocyclopentane and tetrafluoroterephthalic acid in a molar ratio of 1:1, adding them into a 100 mL round-bottom flask, adding 4.0 mL of anhydrous ethanol solution into the round-bottom flask, heating to 70° C., refluxing and stirring at this temperature for 9 hours, and stopping heating to obtain a blue clear reaction liquid;
[0040] S2. The reaction solution was cooled at room temperature and then filtered. The solution was transferred into a 10 mL clean glass vial, sealed with plastic wrap, and 6 small holes were pierced in the plastic wrap with a needle. The solution was evaporated at room temperature for 9-14 days to obtain a diarylethene hydrogen-bonded organic framework single crystal PDTE-TA.
[0041] The present invention has carried out a number of measurements and experiments on PDTE-TA, specifically including the following measurements and experiments:
[0042] 1) Crystal measurement: The PDTE-TA crystal material prepared in Example 1 was subjected to crystal measurement.
[0043] Test method: The diffractometer was used at room temperature using a Bruker SMART APEX II single crystal diffractometer and refined using the SHELX-2014 program and the full matrix least squares method. All non-hydrogen atoms were anisotropically refined. During the refinement process, the SQUEEZE program in PLATON was used to remove the disordered guest molecules.
[0044] like Figure 2 As shown, the crystal structure of PDTE-TA. The diarylethene hydrogen-bonded organic framework single crystal is assembled from 1,2-di[2-methyl-3-thienyl-5-pyridyl]perfluorocyclopentane and tetrafluoroterephthalic acid; the diarylethene hydrogen-bonded organic framework single crystal belongs to the monoclinic system, the space group is C2 / c, the unit cell parameters are a=21.437(8)b=8.418(3)c=19.277(7); α=90°, β=114.343(6)°, γ=90°.
[0045] The structural formula of the 1,2-bis[2-methyl-3-thienyl-5-pyridyl]perfluorocyclopentane is:
[0046]
[0047] The structural formula of the tetrafluoroterephthalic acid is:
[0048]
[0049] 2) Thermal stability test: The PDTE-TA crystal material prepared in Example 1 was subjected to a thermal stability test.
[0050] Test method: The thermal stability of the samples was investigated by heating from room temperature to 800°C at a heating rate of 10°C / min in a nitrogen atmosphere using a Netzsch STA 449C thermogravimetric analyzer.
[0051] like Figure 3 As shown, PDTE-TA experienced two mass losses, indicating the decomposition of [1,2-bis[2-methyl-3-thienyl-5-pyridyl]perfluorocyclopentane and tetrafluoroterephthalic acid, respectively, and was stable before decomposition at 200 °C.
[0052] 3) Infrared spectrum test: The PDTE-TA crystal material prepared in Example 1 was subjected to infrared spectrum test.
[0053] Test method: Use dry KBr to press the tablets, and record the infrared spectrum in the wave number range of 4000-400cm-1 on a Bruker Vertex-70 Fourier transform infrared spectrometer. Compare the infrared data of PDTE-TA, PDTE and TA.
[0054] like Figure 4 As shown in the figure, the change of the -OH (2500-3100) vibration band in the carboxyl group (-COOH) in the infrared spectrum of PDTE-TA indicates the formation of hydrogen bonds between PDTE and TA. The infrared spectrum verifies the formation of PDTE-TA crystals.
[0055] 4) X-ray diffraction test: The PDTE-TA crystal material prepared in Example 1 was subjected to an X-ray diffraction test.
[0056] Test methods: Powder X-ray diffraction (PXRD) characterization was performed on a Malvern Panalytical Empyrean X-ray diffractometer using Cu radiation in the 2θ range of 5°C-50°C at room temperature to determine the purity of the sample and whether the structure of the crystal has changed.
[0057] like Figure 5 As shown, the spectra of the open-ring PDTE-TA-o and closed-ring PDTE-TA-c of the experimentally synthesized samples before and after illumination are in good agreement with the PXRD patterns simulated by Mercury single crystal data, indicating that the synthesized crystalline PDTE-TA has a high phase purity.
[0058] 5) Solid-state ultraviolet absorption spectrum test: The PDTE-TA crystal material prepared in Example 1 was subjected to a solid-state ultraviolet absorption spectrum test.
[0059] Test method: When using the SHIMADZU UV-2700i to test the UV absorption spectrum of solid samples, first prepare the sample and ensure that it is clean and uniform. Then, use the reflection accessory to measure and select the appropriate spectral range (200-800nm). Use the reflection mode to collect spectral data during the test. After the test, convert the data from reflection to absorption on the instrument, and then export the data to plot using Ori gin.
[0060] like Figure 6 As shown in Figure 2, the changes in the absorption characteristics of PDTE-TA before and after UV irradiation indicate that the material has undergone photochromic changes.
[0061] 6) Nitrogen gas adsorption experiment: A nitrogen gas adsorption experiment was performed on the PDTE-TA crystal material prepared in Example 1.
[0062] Test method: Place the sample in an oven at 100°C for 8 hours to complete the activation of the sample. After activation, the sample enters the gas adsorption device. Perform nitrogen gas adsorption-desorption test to test the nitrogen adsorption-desorption test from open loop to closed loop before and after PDTE-TA illumination.
[0063] like Figure 7 As shown, the opening and closing of the diarylethene rings leads to changes in the pores and structure of the material, causing the specific surface area to change from 6.073 m2 / g to 15.970 m2 / g, indicating that the opening and closing of the material rings can significantly lead to changes in the gas specific surface area.
[0064] 7) Single component vapor adsorption experiment: The PDTE-TA crystalline material prepared in Example 1 was subjected to single component vapor adsorption experiments of pyridine and toluene.
[0065] Test method: Place the sample in an oven at 100°C for 8 hours to complete the activation of the sample. The activated sample adsorbs single-component pyridine and toluene: Take a 20mL sealed glass vial, add 1mL pyridine, take 10mg of the activated sample and place it in a 5mL open glass vial, and place the 5mL open glass vial in the 20mL sealed glass vial containing the pyridine solution; Take a 20mL sealed glass vial, add 1mL toluene, take 10mg of the activated sample and place it in a 5mL open glass vial, and place the 5mL open glass vial in the 20mL sealed glass vial containing the toluene solution, and monitor the 1H NMR of the adsorption of pyridine and toluene over time.
[0066] like Figure 8 As shown, by comparing the 1H NMR of PDTE-TA adsorbing pyridine and toluene respectively, it is found that PDTE-TA can adsorb about 2 pyridine molecules, and the adsorption of toluene is almost negligible, that is, the adsorption capacity of PDTE-TA for pyridine is significantly stronger than that for toluene.
[0067] 8) Two-component vapor adsorption experiment: The PDTE-TA crystal material prepared in Example 1 was subjected to a two-component vapor adsorption experiment of pyridine and toluene.
[0068] Test method: Place the sample in an oven at 100°C for 8 hours to complete the activation of the sample. The activated sample adsorbs a mixed system of two components of pyridine and toluene (volume ratio 1:1): Take a 20mL sealed glass vial, add 1mL pyridine and 1mL toluene, take 10mg of the activated sample and place it in a 5mL open glass vial, place the 5mL open glass vial in the above 20mL sealed glass vial containing the pyridine and toluene mixed solution, and monitor the 1H NMR of the adsorption of pyridine and toluene mixed solution over time.
[0069] like Fig. 9 As shown in Figure 3, the time-dependent solid-gas adsorption isotherm of PDTE-TA adsorbing two-component pyridine and toluene mixed vapor shows that PDTE-TA can adsorb about 2 pyridine molecules, and the adsorption of toluene is almost negligible, that is, PDTE-TA has good adsorption selectivity for pyridine.
[0070] 9) Two-component gas chromatography test: The PDTE-TA crystalline material prepared in Example 1 was subjected to a two-component gas chromatography test for adsorption of pyridine and toluene.
[0071] Test method: Place the sample in an oven at 100°C for 8 hours to complete the activation of the sample. The activated sample adsorbs a mixed system of two components of pyridine and toluene (volume ratio 1:1): Take a 20mL sealed glass vial, add 2mL pyridine and 2mL toluene, take 50mg of the activated sample and place it in a 5mL open glass vial, place the 5mL open glass vial in the above 20mL sealed glass vial containing the pyridine and toluene mixed solution, and use Trace1300 gas chromatograph to test the adsorption content of pyridine and toluene after the sample adsorbs the pyridine and toluene mixed solution (volume ratio 1:1) to saturation.
[0072] like Fig.10 As shown, the proportion of pyridine in PDTE-TA was determined to be 97.4% by gas chromatography (GC) experiment, indicating that PDTE-TA has high adsorption selectivity and separation effect for pyridine.
[0073] 10) Repeated test of adsorption of pyridine and toluene. In this example, the PDTE-TA crystalline material prepared in Example 1 was subjected to repeated test of adsorption of pyridine and toluene to study the repeatability of the material.
[0074] Test method: After PDTE-TA adsorbs the mixed gas of pyridine and toluene, it is heated at 120°C for 12 hours to remove the mixed gas of pyridine and toluene. The desorbed and recovered PDTE-TA can be repeated for the 9 experiments.
[0075] like Fig.11 As shown in the figure, the performance of PDTE-TA in separating the mixture of pyridine and toluene was not reduced after recycling for 5 times, indicating that the PDTE-TA material is stable enough to be reused.
[0076] Therefore, regarding the application of the diarylethene hydrogen-bonded organic framework single crystal provided by the present invention, the diarylethene hydrogen-bonded organic framework single crystal can be used to adsorb and separate pyridine and toluene in a mixture of pyridine and toluene liquid after activation, and Experiment 9 shows that PDTE-TA has high adsorption selectivity and separation effect for pyridine.
[0077] The above description is only a preferred embodiment of the present invention and does not limit the present invention in other forms. Any technician familiar with the profession may use the technical content disclosed above to change or modify it into an equivalent embodiment with equivalent changes and apply it to other fields. However, any simple modification, equivalent change and modification made to the above embodiment based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A diarylethene hydrogen-bonded organic framework single crystal, characterized in that: The invention is composed of 1,2-di[2-methyl-3-thienyl-5-pyridyl]perfluorocyclopentane and tetrafluoroterephthalic acid; the diarylethene hydrogen bond organic framework single crystal belongs to the monoclinic system, the space group is C2 / c, the unit cell parameters are a=21.437(8)b=8.418(3)c=19.277(7); α=90°, β=114.343(6)°, γ=90°; The structural formula of the 1,2-bis[2-methyl-3-thienyl-5-pyridyl]perfluorocyclopentane is: The structural formula of the tetrafluoroterephthalic acid is:
2. A method for synthesizing a diarylethene hydrogen-bonded organic framework single crystal, characterized in that: The following steps are involved: S1. Add a certain molar ratio of 1,2-bis[2-methyl-3-thienyl-5-pyridine]perfluorocyclopentane and tetrafluoroterephthalic acid into a 100 mL single-necked flask, add a certain volume of organic solvent into the flask, and heat for a certain period of time until the raw materials are completely dissolved to obtain a reaction solution; S2. The reaction solution was cooled at room temperature and then filtered, and transferred into a 10 mL glass vial, which was sealed with plastic wrap. Appropriate small holes were pierced in the plastic wrap with a needle, and the solution was allowed to stand at room temperature for a period of time to evaporate, thereby obtaining a diarylethene hydrogen-bonded organic framework single crystal PDTE-TA.
3. The method for preparing a diarylethene hydrogen-bonded organic framework single crystal according to claim 2, characterized in that: In step S1, the molar ratio of 1,2-bis[2-methyl-3-thienyl-5-pyridyl]perfluorocyclopentane to tetrafluoroterephthalic acid is 1:
1.
4. The method for preparing a diarylethene hydrogen-bonded organic framework single crystal according to claim 3, characterized in that: The organic solvent is anhydrous ethanol, and the volume of the organic solvent is 3-5 mL.
5. The method for preparing a diarylethene hydrogen-bonded organic framework single crystal according to claim 4, characterized in that: In step S1, the heating temperature is 70°C and the heating time is 9 hours.
6. The method for preparing a diarylethene hydrogen-bonded organic framework single crystal according to claim 5, characterized in that: The number of small holes in the cling film is 1-8, and the hole diameter is less than 3 mm.
7. The method for preparing a diarylethene hydrogen-bonded organic framework single crystal according to claim 6, characterized in that: The reaction solution is allowed to stand at room temperature for 9 to 14 days for volatilization.
8. An application of a diarylethene hydrogen bonded organic framework single crystal, characterized in that: The diarylethene hydrogen-bonded organic framework single crystal is activated at 100° C. for 8 hours to obtain an activated crystal, and the activated crystal is used to separate polar and non-polar substances in a mixture of polar and non-polar substances.
9. The use of a diarylethene hydrogen-bonded organic framework single crystal according to claim 8, characterized in that: The activated crystals are placed in a mixture of polar and non-polar substances and the volatile gas is adsorbed and separated at room temperature for a time of 0-44 hours.
10. Use of a diarylethene hydrogen-bonded organic framework single crystal according to claim 8 or 9, characterized in that: The polar and non-polar substance mixture liquid is a pyridine and toluene mixture liquid.
Citation Information
Patent Citations
Fluorine-containing metal-organic framework, preparation method thereof and application in adsorption of perfluorooctanoic acid
CN110237819A
Method of making mixture of polymers
CN112352006A
Novel photochromic metal-organic framework material as well as preparation method and application thereof
CN116769176A
Photochromic diarylethene compound as well as preparation method and application thereof
CN119101029A
Krypton gas separation compound as well as preparation method and application thereof
CN119176823A